Pengembangan Media Rotasi Dinamis untuk Membangun Kemampuan Literasi Numerasi pada Pembelajaran Transformasi - Lakoy, Felix Arnold (Jurnal Didaktika Pendidikan Dasar, 2022)
This study aims to determine the development of dynamic rotation media that is valid, practical, effective, and how this media can develop numeracy literacy. The media was applied to class IX students consisting of 22 students. Media development uses research and development methods (Research and Development) with a 4D model, which stands of Define, Design, Development and Dissemination. It is known that the results of the validity test from material experts are 3.04 and from media experts are 3.05, meaning that the developed media is valid for use. For the practicality test, it is obtained at 3.3 which indicate that the media used is practical. From the effectiveness test, it was obtained that the average value of the numeracy literacy test was 84.16 and the classical completeness was 100% which had met the effectiveness criteria. After the application of this media resulted in the numeracy literacy ability reaching an average of 75.57 and classical learning completeness data of 86.36%, the student response questionnaire with a score of 3.27 which indicates a positive category. Based on the validity test, practicality test, and effectiveness test, the dynamic rotation media met the criteria of being valid, practical, and effective. The media used in the learning process shows that dynamic rotation media can improve numeracy literacy skills in transformation learning.